Gender Gap in Science, Technology, Engineering and Mathematics (STEM): Barriers and Solutions - Alawi, Wahiba Sayed Saeed; Al Mubarak, Muneer Mohamed (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to identify and discuss barriers facing females in the fields of science, technology, engineering and mathematics (STEM). The study looks at three developmental stages; first, school life (childhood) stage between the age of 6 and 18, second, university life (adulthood) stage from the age of 18 and 22, and third, professional life (maturity) stage from the age of 22 and above. The main findings are stereotyping and society’s perception to women that lead to classification of roles and responsibilities based on gender. Parents and teachers’ expectations, parents’ profession, and community culture are the most factors that influence the childhood stage. Stereotyping, and low number of females in the classroom are characterized in the adulthood stage. The most important factors in the maturity stage are: (1) bias against women at work, (2) discouraging work environment for women, and (3) childbirth and maternity barriers. Few studies detailed gender barriers in STEM, especially in the region. In the light of these barriers, appropriate suggestions are put forward to overcome such barriers at each stage. Keywords: Science, Technology, Engineering and Mathematics, Gender, School Life, University Life, Professional Life JEL Classifications: I20, I24 DOI: https://doi.org/10.32479/ijefi.8908